2020
DOI: 10.3390/asi3010012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nanofluids Behavior in a PV-Thermal-Driven Organic Rankine Cycle with Cooling Capability

Abstract: This paper discusses the performance of nanofluids in a PV Thermal-driven Organic Rankine Cycle (ORC) with cooling capabilities. This study was intended to investigate the enhancement effect and characteristics of nanofluids; Al2O3, CuO, Fe3O4 and SiO2 on the performance the hybrid system composed of PV Thermal, ORC and cooling coil. The quaternary refrigerant mixture used in the ORC cycle to enhance the ORC efficiency is an environmentally sound refrigerant mixture composed of R152a, R245fa, R125, and R1234fy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The utilization of graphene and carbon nanotubes aqueous nanofluids as engine coolant enhanced waste heat recovery, having a net power output of nearly 3.8 in two different organic Rankine cycle configurations [117]. The use of silica, alumina, copper oxide, and iron oxide aqueous nanofluids for cooling photovoltaic panels to drive the organic Rankine cycle revealed a 17% enhancement in the efficiency of the system with copper oxide aqueous nanofluids [118]. Also, multi-walled carbon nanotubes dispersed in oil have been used for solar energy storage from solar concentrators attaining a total system efficiency of 21.4% in reference to that of 18.9% attained with the oil base fluid alone [119].…”
Section: Heat-to-work Waste Heat Recovery With Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of graphene and carbon nanotubes aqueous nanofluids as engine coolant enhanced waste heat recovery, having a net power output of nearly 3.8 in two different organic Rankine cycle configurations [117]. The use of silica, alumina, copper oxide, and iron oxide aqueous nanofluids for cooling photovoltaic panels to drive the organic Rankine cycle revealed a 17% enhancement in the efficiency of the system with copper oxide aqueous nanofluids [118]. Also, multi-walled carbon nanotubes dispersed in oil have been used for solar energy storage from solar concentrators attaining a total system efficiency of 21.4% in reference to that of 18.9% attained with the oil base fluid alone [119].…”
Section: Heat-to-work Waste Heat Recovery With Nanofluidsmentioning
confidence: 99%
“…The authors noted that the organic Rankine cycle with copper oxide nanofluids demonstrated a better economic performance than that demonstrated by the alumina nanofluids. Furthermore, the author Sami [118] studied the thermal performance of a hybrid system composed of photovoltaic/thermal, organic Rankine cycle, and cooling coil using silica, alumina, copper oxide, and iron oxide nanofluids in a waste heat boiler of the organic Rankine cycle. Among the different heat transfer fluids, the copper oxide nanofluids provided the highest efficiency and greater cooling effect, increasing the efficiency of the hybrid system by around 17%.…”
Section: Heat-to-work Waste Heat Recovery With Nanofluidsmentioning
confidence: 99%
“…Currently, the efficiency of commercial solar PV is up to 15%, and most of the incoming solar radiation energy is either absorbed or reflected and significant excess heat is dissipated and wasted. To improve the solar PV's efficiency a novel concept of combined photovoltaic-thermal solar panel hybrid system concept using nanofluids has been developed [1][2][3][4][5][6][7][8][9][10][11]. It is a simple hybrid system where the PV cells are cooled through water-based nanofluids flows.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids have excellent thermal conductivity [1][2][3][4][5][6][7][8][9][10][11] and have been applied as the working fluids in traditional heat pipe applications to enhance thermal performance. "In the presence of an external magnetic field, the thermal conductivity of magnetite nanofluids increases with the increase in the volumetric concentration of magnetic particles, which is associated with the increase in the magnetic field strength" [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%